Tourism Development Strategy for Effectiveness Expanding Chinese Outbound Tourism Market: A Case Study of Lanna Culture Tourism Development Region - Onkaew , Sutima (Dusit Thani College Journal, 2020)
The objective of this research was to determine tourism development strategies for effectively extending tourism marketing of Chinese tourists: case study of the tourism development of Lanna civilization area from synthesizing information from three subprojects as follows: 1) Approaches for Printed Media Development to Accomplish Social Rule and Cultural Understanding in Lanna Culture for Chinese Tourists: Case Study - Lanna Culture Tourism, 2) Tourism Development Strategy for Effectiveness Expanding Chinese Outbound Tourism Market: Case Study-Culture Tourism Development Region, and 3) Tourism Marketing Strategy for Chinese Tourists: Case Study - Lanna Culture Tourism Development Region, conducting the SWOT Analysis of tourism development, and applying the two-sided natural mechanism based on Edward De Bano’s thinking Method indicating that there were two sides of every coin, which meant weaknesses could turn to strengths (W"S) and threats could turn to opportunities (T"O). Consequently, only strengths and opportunities (SO) remained, and helped business establish “The Golden Minute Stage” strategy. It was generally known that strategy is planning ahead to the step beyond others. Strategy also indicates vision generating value creation. All information mentioned above led to the tourism development strategy for effectively extending the tourism marketing of Chinese tourists or called HOST, which means a good host as details follow; H - Hospitality meant creating the impression to Chinese tourists by providing them with service mind “They do not know. How to help them get a better understanding?” O - Old Culture meant maintaining the Lanna civilization by learning about the culture through places, foods and the way of life and creating the common understanding with Chinese tourists by providing them for a better knowing and understanding towards the old culture then they may tell others. S - Sustainable meant many tourism activities moved by communities. Therefore, communities had earned from tourists in traditional performances and souvenirs, which means Consequently, the culture was a selling point for Chinese tourist groups. T - Teammate meant the collaboration among government agencies, private sector, educational institutions and communities, including the participation of Chinese tourists who joined in the creative travelling and did not destroy the old cultures. The mentioned collaborations led to a sustainable tourism.